HUBUNGAN SELF EFFICACY DENGAN WORK READINESS PADA MAHASISWA SEMESTER TINGKAT AKHIR STRATA SARJANA DI KOTA PADANG - Bima Nanda Pratama; Nio, Suci Rahma; Dwatra, Free Dirga; Guspa, Anindra (CV. Causalita Dynamic Solutions, 2023)
The aim of this research is to look at the relationship between self-efficacy and work readiness in final year undergraduate students in the city of Padang. This type of research is quantitative research with a population of final year undergraduate students in Padang City with a sample size of 272 students. The sampling technique used in this research was purposive random sampling. Using a Likert scale with 4 (four) answer choices, namely Strongly Agree (SS), Agree (S), Disagree (TS), Strongly Disagree (STS) with 30 question items from both variables. The analysis used is correlation product moment with a value of r=0.443 and a value of p=0.00 (p<0.05) with the meaning of Ha being accepted that there is a positive relationship between self-efficacy and work readiness in final semester undergraduate undergraduate students in the city of Padang.